2006
DOI: 10.1037/0278-7393.32.5.1057
|View full text |Cite
|
Sign up to set email alerts
|

How do highly proficient bilinguals control their lexicalization process? Inhibitory and language-specific selection mechanisms are both functional.

Abstract: The authors report 4 experiments exploring the language-switching performance of highly proficient bilinguals in a picture-naming task. In Experiment 1, they tested the impact of language similarity and age of 2nd language acquisition on the language-switching performance of highly proficient bilinguals. Experiments 2, 3, and 4 assessed the performance of highly proficient bilinguals in language-switching contexts involving (a) the 2nd language (L2) and the L3 of the bilinguals, (b) the L3 and the L4, and (c) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
418
7
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(486 citation statements)
references
References 75 publications
57
418
7
4
Order By: Relevance
“…The findings of our study also seem to be in good agreement with the evidence of DLPFC involvement in other cognitive switching tasks [7,20] and executive control in general [3,13,31]. Language switching involves competition between language task schemas which are responsible for the enhancement of the correct language and suppression of the incorrect language [14], and involves lexical selection of words in the target language and may involve inhibition of the non-target language [4,5]. Verhoef et al [32] recently demonstrated that inhibition, even if not necessary, can modulate the efficiency of language switching.…”
Section: Article In Presssupporting
confidence: 89%
“…The findings of our study also seem to be in good agreement with the evidence of DLPFC involvement in other cognitive switching tasks [7,20] and executive control in general [3,13,31]. Language switching involves competition between language task schemas which are responsible for the enhancement of the correct language and suppression of the incorrect language [14], and involves lexical selection of words in the target language and may involve inhibition of the non-target language [4,5]. Verhoef et al [32] recently demonstrated that inhibition, even if not necessary, can modulate the efficiency of language switching.…”
Section: Article In Presssupporting
confidence: 89%
“…If there is a difference in proficiency between the two languages, the switch cost should be asymmetric because more inhibition would be required to suppress the stronger language not in use. However, as discussed in Section 1, symmetric switch costs have been found between L1 and a much weaker L3 in early, high-proficient, balanced bilinguals (Calabria et al, 2012;Costa & Santesteban, 2004;Costa et al, 2006), as well as in unbalanced bilinguals who have daily practice of often switching languages (Christoffels et al, 2007). These previous data suggest that in bilinguals exposed to daily switching, the mechanisms of bilingual language control may be at least partly independent of domain-general cognitive control.…”
Section: Discussionmentioning
confidence: 84%
“…This result is consistent with Calabria et al (2012) who found asymmetric and symmetric switch costs in non-linguistic mixed-task and mixed-language conditions, respectively (see Section 1). Some researchers have attributed switch costs to an inhibition mechanism (Green, 1998;Meuter & Allport, 1999; see however Costa & Santesteban, 2004;Costa, Santesteban, & Ivanova, 2006;Verhoef, Roelofs, & Chwilla, 2009): that is, inhibition is used to suppress the non-target language during a trial. This would lead to a cost of switching target language as inhibition has to be overcome.…”
Section: Discussionmentioning
confidence: 99%
“…Highly proficient and balanced bilinguals in that study produced a symmetric pattern of switch costs, but they also produced longer naming latencies for the L1 than the L2, a result that suggested the presence of L1 inhibition. A later study (Costa, Santesteban, & Ivanova, 2006) replicated the symmetrical pattern for proficient bilinguals but also showed that proficiency alone was sufficient to produce symmetry; it was not necessary that they also be early bilinguals. Wodniecka et al (in preparation) first demonstrated that the asymmetric vs. symmetric pattern of switch costs in picture naming could be replicated in two groups of late bilinguals who differed in whether they were dominant in the L1 or relatively balanced across the two languages.…”
Section: Language Switchingmentioning
confidence: 88%